46. KNOWLEDGE, PRACTICE OF REFRACTIVE ERROR PREVENTION AND SOME RELATED FACTORS OF FIRST-YEAR STUDENTS AT NGUYEN TAT THANH UNIVERSITY, IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the knowledge, practice of refractive error prevention and some related factors of first-year students at Nguyen Tat Thanh University, in 2024.Methods: A descriptive cross-sectional design was conducted on 349 first-year students at Nguyen Tat Thanh University from April 2024 to August 2024.Results: The percentage of first-year students with correct general knowledge about refractive error prevention was 71.1%, and correct general practice about refractive error prevention was 52.2%. Some factors related to students' practice about refractive error prevention included (p < 0.05): Gender, age group, ethnicity, major, and general knowledge about refractive error prevention. The rate of students with correct practice in preventing refractive errors in the group studying other majors (economics, engineering) was lower than that in the group studying health majors (OR = 0.12; 95% CI: 0.08 - 0.19), the group with incorrect knowledge was lower than that in the group with correct knowledge (OR = 0.20; KTC 95%: 0.12 – 0.33).Conclusion: First-year students had relatively good knowledge about refractive error prevention (71.1%), but their practice of refractive error prevention was not high (52.2%). The rate of proper refractive error prevention practices was lower among students from other majors and those with incorrect knowledge.
Keywords: Refractive errors; knowledge; attitudes; related factors